Pengaruh Kurs, Inflasi, Ekspor dan Impor terhadap Pertumbuhan Ekonomi di Negara Austria Tahun 2000 – 2020 - Andi Triyawan; Sya’na Sekar Izaty (LPPM Universitas BSI, 2022)
This research aims to analyze the effect of Exchange Rate, Inflation, Exports and Imports on Economic Growth in Austria in 2000–2020. The method used in this study is Multiple Linear Regression. Exchange rate data, exports and imports were taken from the Worldbank (World Bank), Inflation data was taken from the IMF. The results showed that the exchange rate, inflation, exports and imports had no effect on economic growth in Austria. Likewise with a partial test of the exchange rate which has a positive effect on economic growth in Austria, inflation does not have a significant effect on economic growth, the level of exports does not have a significant effect on economic growth in this country, and imports have a positive and significant effect on economic growth. in GDP countries. Keywords: Inflation, Export, Import, Economic Growth